تأثير تغيير الاحمال الكهربائية على ضياع الاستطاعة عند انحراف التوتر عن القيمة الاسمية - جورج اسبر (Tishreen University, 2022)
تأثير تغيير الاحمال الكهربائية على ضياع الاستطاعة عند انحراف التوتر عن القيمة الاسمية